Penerapan Fungsi Manajemen di Koperasi (Studi pada Desa Nanggungan Kecamatan Kayen Kidul Kabupaten Kediri) - Rr. Endang Sri Handini; Rizky Fillya Curtinawati; Alfi Mustofa (FISIP UWP, 2023)
The success of a cooperative business cannot be separated from management in managing a business, the quality of management in a cooperative must have good human resource capabilities. management is the core of a cooperative body, to achieve the objectives of the cooperative good management is needed so that the success of the cooperative is realized. Harmony Women's Cooperative is one of the cooperatives that in its implementation must have good management in order to successfully achieve its goals. However, due to Covid-19 there is a decrease in managerial activities in the Cooperative. This research uses descriptive with a qualitative approach. The results of this study are from five management functions 4 of which are planning, organizing, directing and supervising have been running well but for coordination and communication are very weak such as the lack of active cooperative members. So it can be concluded that the management function in the Harmony Women's Cooperative is quite good, only needs to be improved for the coordination and communication functions.